Perception and Experience of Teachers in Implication of Inductive and Deductive Methods in Mathematics Classes - Sapkota, Hari Prasad (Journal of Mathematics Education, 2023)
This paper aims to explore the teachers’ experiences and perceptions towards the implication of inductive and deductive methods in mathematics classes at the primary level. The inductive method is the beginning of all mathematics and derives the formula; the deductive method is the continuity of it and implements those formulas. This article is based on a phenomenological research method under qualitative design, focusing on the lived experience of four primary mathematics teachers on the ‘implementation of inductive and deductive method’ in elementary mathematics classes and their perceptions towards these methods. The data were analyzed and interpreted by using the thematic analyzing approach. The findings of the study show that the teachers were in a dilemma in the selection of proper teaching methods in mathematics teaching, and they followed the traditional methods. Knowingly or unknowingly, the teachers were using inductive and deductive methods, but they were not sure about the correct implementation of those methods. Their perceptions towards the inductive method was positive and they believed that it helps students for developing permanent concepts; however, the teachers were confused in its implications. Most of the teachers were following the traditional teaching methods in mathematics classes instead of student-centered teaching methods. They argued that for a short-cut and easy for the implementation, they were using the traditional methods. The teachers should be trained for better implementation of the inductive and deductive methods in the proper teaching of mathematics at the primary level.